Ecotourism industry in India: a review of current practices and prospects. Issue 2 (3rd April 2021) - Pujar, Sachin C.; Mishra, Niharranjan
ABSTRACT: The current study examines ecotourism as practiced in India by conducting a descriptive literature review of studies published between 1990 and 2019, focusing on ecotourism's conservation and development goals. The findings of the study have been categorized on the basis of Honey's classification of ecotourism to provide a better understanding of current ecotourism practices in India. The paper concludes that the Indian ecotourism industry, with apparent conservation and commercial bias, might become unsustainable in the long run. The study highlights the need to revise ecotourism planning and management to ensure a long-term sustainable tourism model. This review adds to the existing body of literature in ecotourism by highlighting the progress and the shortcomings of the niche industry.